Era Disrupsi Teknologi dan Sikap Pemimpin Kristen - Adi Saingo, Yakobus (IAKN TORAJA, 2023)
Abstract: This study aims to discuss the existence of the era of technological disruption and the attitude of Christian leaders in facing various challenges. This study applies a qualitative method in the form of library research in which information is collected from various literatures whose content is still relevant to the research topic. The data were analyzed descriptively which presented the results that in the challenges of the era of technological disruption as it is today, it is necessary to have a form or form of Christian leadership as the vanguard in preparing God's people to become individuals who continue to uphold moral, social and spiritual values. There are various forms of Christian leaders' attitudes towards technological disruption, including: living a spiritual attitude, an educative attitude, an attitude of integrity, an attitude of the principle of benefit, a humanistic attitude. These attitudes must be taught, instilled and exemplified by Christian leaders in every institution where they take shelter so that they are able to promote a life of self-control in the correct use of technology, and make technological disruption as a means and opportunity to introduce Christ to many people unlimitedly. Keywords: Era of Disruption, Christian Leaders, Technology. Abstrak: Penelitian ini bertujuan untuk membahas mengenai keberadaan era disrupsi teknologi dan sikap pemimpin Kristen dalam menghadapi berbagai tantangannya. Penelitian ini menerapkan metode kualitatif dalam bentuk library research yang penghimpunan informasinya bersumber dari berbagai literatur yang konten masih relevan dengan topik penelitian. Data dianalisis secara deskriptif yang memaparkan hasil bahwa dalam tantangan era disrupsi teknologi seperti saat ini maka perlu ada wujud atau bentuk sikap pemimpin Kristen sebagai garda terdepan mempersiapkan umat Allah menjadi pribadi yang tetap menjunjung nilai-nilai moral, sosial maupun spiritual. Adapun berbagai bentuk sikap pemimpin Kristen memasuki disrupsi teknologi, antara lain: menghidupi sikap spiritual, sikap edukatif, sikap integritas, sikap asas manfaat, sikap humanistik. Sikap-sikap tersebut harus diajarkan, ditanamkan dan diteladankan oleh pemimpin Kristen dalam setiap lembaga tempatnya bernaung sehingga mampu mempromosikan kehidupan pengendalian diri dalam penggunaan teknologi secara benar, serta menjadikan disrupsi teknologi sebagai sarana maupun kesempatan memperkenalkan Kristus bagi banyak orang secara tidak terbatas. Kata Kunci: Era Disrupsi, Pemimpin Kristen, Teknologi.